A practical guide to IFRS for derivatives and structured finance - Tosen, Graeme (London : Euromoney Books, 2006)
A guide which helps readers understand and implement the technical accounting rules of the International Financial Reporting Standards (IFRS) that apply to derivatives and structure finance. It is intended as a reference for practitioners needing to interpret and apply the rules to derivatives, structured finance and securitisations.
oif 30/03/15
Loan
Keywords: International financial reporting standards; Derivative securities -- Accounting -- Standards; Financial instruments -- Accounting -- Standards; Comparative accounting